Data bases and discrete event simulation - Boubetra, Abdelhak (2007)
This paper is an attempt to define how a specific data structure might be used to store, in a persistent manner, temporal information during a computer simulation. In particular, it considers the sort of temporal information generated during a discrete event simulation of a system to which a relational data base exists and considers the demands this data makes on data base design.